The lifetime medical cost savings from preventing HIV in the United States. - Schackman, Bruce R; Fleishman, John A; Su, Amanda E; Berkowitz, Bethany K; Moore, Richard D; Walensky, Rochelle P; Becker, Jessica E; Voss, Cindy; Paltiel, A David; Weinstein, Milton C; Freedberg, Kenneth A; Gebo, Kelly A; et al. (Medical care, 2015)
Enhanced HIV prevention interventions, such as preexposure prophylaxis for high-risk individuals, require substantial investments. We sought to estimate the medical cost saved by averting 1 HIV infection in the United States.
Keywords: Adolescent; Adult; Anti-Retroviral Agents; CD4 Lymphocyte Count; Computer Simulation; Cost Savings; Health Care Costs; HIV Infections; Humans; Middle Aged; Models, Economic; United States; Young Adult